الآثار الاقتصادية والاجتماعية لغسيل الأموال - العمار رضوان; يازجي أمل; حاج طه طه أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
قد يعتقد بعضهم أن عمليات غسيل الأموال لها آثار إيجابية خاصة في حالة اتخاذها الصورة العينية, مثل إقامة شركات استثمار وتوفير العديد من فرص العمل والمساهمة في علاج مشكلة البطالة. ويمكن الرد على ذلك ببساطة بأن عدم مشروعية الدخل الناتج عن عمليات غسيل الأموال والذي يمثل قوة شرائية غير ناتجة عن نشاط اقتصادي حقيقي يؤدي إلى آثار سلبية على الاقتصاد المحلي ويسهم في حدوث ضغوط تضخمية تهدد مستقبل التنمية الاقتصادية والاجتماعية. إن بعض الإيجابيات التي تتحقق من استخدام الأموال المغسولة لا يمكن أن تبرر أو تتعادل مع فداحة الآثار السلبية الناتجة عنها. وبناءً على ما تقدم, فإن البحث يتناول الآثار الاقتصادية والاجتماعية الناتجة عن عمليات غسيل الأموال. Some may think that money laundering has positive effects in case it is considered in its concrete forms such as establishing investment companies, creating job opportunities and participating in solving the problem of unemployment. This can be answered through the fact that the illegitimacy of the income resulted from money laundering, which represents purchase power not resulted from a real economic activity, leads to negative effects on the national economy and contributes in creating inflation pressure that threatens the future of the economical and social development. Some advantages gained by using laundered money cannot justify or be equal with the enormity of the disadvantages resulted from it. On this bases, this paper deals with the economic and social effects resulted from the operations of money laundering.